Cardiac dimensions and function in female handball players - Malmgren, A.; Dencker, M.; Stagmo, M.; Gudmundsson, P. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Long-term intensive endurance training leads to increased left ventricular mass and increased left ventricular end-diastolic and left atrial end-systolic diameters. Different types of sports tend to give rise to distinct morphological forms of the athlete's heart. However, the sport-specific aspects have not been fully investigated in female athletes. The purpose of the present study was to investigate differences in left and right cardiac dimensions, cardiac volumes, and systolic and diastolic function in elite female handball players compared to sedentary controls.